Analisis Kesadaran Wisatawan terhadap Dampak Sampah di Pantai Ancol Pada Masa Liburan - Nathaniel Septian Prasmono; Wiwik Nirmala Sari (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze tourists' awareness of the impact of waste at Ancol Beach during the holiday season. Waste issues have become a significant environmental concern in tourist areas, particularly during holidays when the number of visitors increases drastically, interviews were conducted with tourists from various linguistic backgrounds to assess their perceptions of beach cleanliness, understanding of waste impact on the environment, and participation in waste management efforts. Primary data were obtained through interviews and direct observation at Ancol Beach, while secondary data were sourced from literature related to waste management in tourist areas. The findings indicate that tourists' awareness levels vary, with significant differences between local and international tourists. Furthermore, although many tourists recognize the negative impact of waste, further educational efforts are needed to enhance participation in maintaining beach cleanliness. This study also highlights the importance of collaboration between tourism managers, the government, and tourists in addressing the waste problem at Ancol Beach.